Inhibitory effects of different hand sanitizers against the resident microflora of skin - Ishma, Touhida; Uddin, H. M. Sayeed; Paul, Anik; Feroz, Farahnaaz; Acharjee, Mrityunjoy (International Journal of Scientific Reports, 2019)
Background: Practice of hand washing is very important to eliminate the microbial contamination especially during the work in laboratories, hospital and even at home before taking food. Proper use of hand sanitizer can significantly reduce the rate of hospital acquired infection also. Methods: The current investigation was designated to identify different bacterial species from the upper skin of hands of the laboratory managements through conventional culture methods and the efficacy of the samples (Dettol, Purell and Savlon) against the isolated bacteria through agar well diffusion method and minimum inhibitory concentration (MIC) Results: Different concentrations such as 25%, 50% and 100% of each of antimicrobial agents showed their antibacterial activity against Staphylococcus spp., Klebsiella spp., E. coli and Pseudomonas spp. those were isolated from the hand. 25% of Dettol exhibited 20 mm zone diameter against Klebsiellaspp. Whereas 25% of Purell and Savlon unveiled 15 mm and 22 mm zone of inhibition against E. coli and Pseudomonas spp. respectively. In case of 100% sample of Dettol, Purell and Savlon, the highest zone diameter was observed as 55 mm, 50 mm and 45 mm against Klebsiella spp., Staphylococcus spp., and E. coli consecutively. The MIC of Dettol sample was 8 µl against Staphylococcus spp., and Pseudomonas spp. In case of Purell, the MIC was 128 µl against Staphylococcus spp., Klebsiella spp. and Pseudomonas spp. were inhibited at 4 µl samples. Conclusions: The in-vitro antibacterial activity of the hand sanitizers was so satisfactory against the isolated bacteria. This finding would be very helpful for the laboratory management in order to minimize the rate of contamination during the research and supervision of the different experiment.